Repeat hepatic resection versus radiofrequency ablation for recurrent hepatocellular carcinoma: retrospective multicentre study. Issue 1 (13th October 2021) - Zhong, J -H; Xing, B -C; Zhang, W -G; Chan, A W -H; Chong, C C N; Serenari, M; Peng, N; Huang, T; Lu, S -D; Liang, Z -Y; Huo, R -R; Wang, Y -Y; et al.
Abstract: Background: The therapeutic value of repeat hepatic resection (rHR) or radiofrequency ablation (RFA) for recurrent hepatocellular carcinoma (HCC) is unknown. This study aimed to investigate the safety and efficacy of rHR or RFA. Methods: This was a retrospective multicentre study of patients with recurrent HCC within the Milan criteria who underwent rHR or RFA at nine university hospitals in China and Italy between January 2003 and January 2018. Survival after rHR or RFA was examined in unadjusted analyses and after propensity score matching (1 : 1). Results: Of 847 patients included, 307 and 540 underwent rHR and RFA respectively. Median overall survival was 73.5 and 67.0 months after rHR and RFA respectively (hazard ratio 1.01 (95 per cent c.i. 0.81 to 1.26)). Median recurrence-free survival was longer after rHR versus RFA (23.6 versus 15.2 months; hazard ratio 0.76 (95 per cent c.i. 0.65 to 0.89)). These results were confirmed after propensity score matching. RFA was associated with lower morbidity of grade 3 and above (0.6 versus 6.2 per cent; P < 0.001) and shorter hospital stay (8.0 versus 3.0 days, P < 0.001) than rHR. Conclusion: rHR was associated with longer recurrence-free survival but not overall survival compared with RFA. Abstract : Repeat hepatic resection and radiofrequency ablation were comparable in overall survival in spite of differences in recurrence-free survival for patients with recurrent hepatocellular carcinoma within Milan criteria.